National and regional effects of RCEP on trade: the application of the WITS-SMART tool with the focus on China - Zhang, Wenjie; Abd Rahman, Muhammad Daaniyall; Utit, Chakrin (University of Kragujevac - Faculty of Economics, 2025)
This paper investigates the effects of RCEP trade creation and trade diversion on China and its sectors, as well as the impact of imports and exports on provinces. The World Bank’s World Integrated Trade Solution Software for Market Analysis and Restrictions on Trade (WITS-SMART) tool with the 2020 data, alongside the OECD Inter-Country Input-Output (ICIO) tables and the Chinese Multi-Regional Input-Output (MRIO) tables based on the 2017 data under two scenarios. The results of the study indicate that trade growth with Japan and South Korea is significant, on the one hand, whereas the trade effects with the ASEAN nations and regions such as Australia and New Zealand are relatively low, on the other. The research emphasizes the disparities between various regions in China, demonstrating that the Eastern coastal provinces obtain more trade benefits than the Central and Western areas. The study highlights the importance of implementing the policies encouraging collaboration in high-growth sectors and developing tailored strategies for regional advancement.